Are There Lasting Impacts of Aid to Poor Areas? Evidence from Rural China - Chen, Shaohua (World Bank, Washington, DC, 2012)
The paper revisits the site of a large, World Bank-financed, rural development program in China 10 years after it began and four years after disbursements ended. The program emphasized community participation in multi-sectoral interventions (including farming, animal husbandry, infrastructure and social services). Data were collected on 2,000 households in project and nonproject areas, spanning 10 years. A double-difference estimator of the program's impact (on top of pre-existing governmental programs) reveals sizeable short-term income gains that were mostly saved. Only modest gains to mean consumption emerged in the longer term-in rough accord with the gain to permanent income. Certain types of households gained more than others. The educated poor were under-covered by the community-based selection process-greatly reducing overall impact. The main results are robust to corrections for various sources of selection bias, including village targeting and interference due to spillover effects generated by the response of local governments to the external aid.